High-performance graphene field-effect transistor platform for on-site schizophrenia-related biomarkers detection - Kim, Seo Jin; Cha, Yeon Kyung; Kim, Kyung Ho; Kim, Gyeong-Ji; Seo, Sung Eun; Kim, Jung In; Kim, Jae Hyeon; Lee, Yeon Kyung; Seo, Minah; Ryu, Yong-Sang; Kim, Se-Hong; Lee, Kyoung G.; et al. (Pergamon Press Ltd., 2026)
Schizophrenia remains challenging to diagnose objectively, as conventional assessments rely on subjective symptom evaluation and are often associated with significant diagnostic delays. In this study, we present a portable, multiplexed graphene field-effect transistor (GFET) biosensor array for the simultaneous and ultrasensitive detection of three schizophrenia-related biomarkers-cortisol, serotonin, and dopamine-at femtomolar concentrations. Fabricated using microelectromechanical systems processes, the array integrates three monolayer graphene channels on a single chip, each covalently functionalized with a specific bioreceptor to ensure high selectivity and minimal cross-reactivity. Real-time monitoring of transfer characteristics enables detection via Dirac point shifts induced by bioreceptor-analyte binding. The GFET platform demonstrates femtomolar-level sensitivity, broad dynamic range, and specificity in both phosphate-buffered saline and artificial serum. Moreover, the system supports real-time, Bluetooth-enabled data transmission, offering a rapid and objective point-of-care tool to complement conventional psychiatric diagnostics. This platform holds promise for reducing diagnostic latency, supporting personalized treatment strategies, and advancing precision mental health care.